2013
DOI: 10.1007/s00464-012-2779-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the financial implications for laparoscopic liver surgery: a single-centre UK cost analysis for minor and major hepatectomy

Abstract: Our data support the cost advantage of the laparoscopic approach for left lateral sectionectomy and the cost neutrality for right hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 26 publications
4
41
0
1
Order By: Relevance
“…28–30 Several published articles have assessed the financial impact of laparoscopic liver resections, comparing them to open surgery. 8–10,31–33 The results that emerged to prove that laparoscopic surgery has an equal or even superior cost efficiency to open surgery. Even though the intraoperative costs are higher, due to the expensive laparoscopic instruments and longer operative times, the lower morbidity and shorter hospital stay reduce the overall hospital costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28–30 Several published articles have assessed the financial impact of laparoscopic liver resections, comparing them to open surgery. 8–10,31–33 The results that emerged to prove that laparoscopic surgery has an equal or even superior cost efficiency to open surgery. Even though the intraoperative costs are higher, due to the expensive laparoscopic instruments and longer operative times, the lower morbidity and shorter hospital stay reduce the overall hospital costs.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the intraoperative costs are higher, due to the expensive laparoscopic instruments and longer operative times, the lower morbidity and shorter hospital stay reduce the overall hospital costs. 8–10,31–33 …”
Section: Introductionmentioning
confidence: 99%
“…Four papers analyzed the outcomes of laparoscopic (LLLS) versus open left lateral sectionectomy (OLLS) [11,[14][15][16]. Abu Hilal et al [17] provided separate comparisons for LLLS versus OLLS and open (ORH) versus laparoscopic right hepatectomy (LRH). Two papers included a mix of minor and major hepatectomy [12,18], while Medbery et al [13] analyzed outcomes for right hepatectomy only.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported no difference in operating room costs between laparoscopic and open hepatic resection, while one study of LLS only reported statistically significant lower costs of LLLS over OLLS [14]. Two studies examining right hepatectomy reported significantly higher operating room costs for LRH compared with ORH [13,17]. Nine studies reported reductions in hospital length of stay (LOS) with laparoscopic hepatic resection compared to patients undergoing open procedures, shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Many other large scale retrospective studies had shown that laparoscopic liver resection for HCC was non inferior to open surgery in terms of oncological outcome (9)(10)(11). Propensity score matching has been an improved method to eliminate bias.…”
mentioning
confidence: 99%